Diamond fraud analysis in detecting financial statement fraud - Diansari, Rani Eka; Wijaya, Arum Tri (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2019)
This study aims to analyze the influence of variable pressure proxied by financial stability, personal financial need, financial targets, external pressure, the opportunity proxied by nature of the industry, ineffective monitoring, rationalization, and capability of the financial statement fraud. The sample used 72 manufactured company listing on the Indonesia Stock Exchange during the 2014-2017 period. Multiple linear regression test is used to test the influence of the independent variable on the dependent variable. The result showed that financial stability, the ratio of the change in total assets, and external pressure, as measured by leverage, showed an influence on financial statement fraud while the personal financial need, financial targets, nature of industry, ineffective monitoring, rationalization, and capability does not influence financial statement fraud.